Haloperidol plus dexamethasone versus dexamethasone alone to prevent postoperative nausea and vomiting in patients undergoing ambulatory surgery: a randomized, controlled and double-blind study - Chaparro Gómez, Luis Enrique; Rivera, María Fernanda; Gallo, Tatiana; González, Nelson Javier (Iatreia, 2008)
BACKGROUND AND GOAL OF THE STUDY: haloperidol is an effective antiemetic drug. We sought to determine whether haloperidol and dexamethasone prophylaxis schemes decrease the incidence of postoperative nausea and vomiting (PONV) in patients undergoing ambulatory surgery. MATERIALS AND METHODS: we enrolled 160 non-smoking females who received a standardized anesthesia technique including 8 mg of dexamethasone at the beginning of surgery. They were then randomized to receive either 1.5 mg of haloperidol (DH group) or placebo (DP group) 30 minutes before the end of surgery. The incidence of PONV was assessed by a blinded investigator at 30 minutes and at 2, 6 and 24 hours in the postoperative period. Analgesic requirements, ocular opening time and sedation were also assessed. The quantitative variables of normal distribution were evaluated with the t-student test and the ones with abnormal distribution, with the U-Mann Whitney test. Qualitative variables were evaluated with the Fisher test. RESULTS AND DISCUSSION: both groups were homogeneous in demographic characteristics (30.1 vs. 29.5 years, 55.9 vs. 56 kg) and history of PONV in 21.5% vs. 21.2% in DH group vs. DP group, respectively). At 6 hours postoperatively we found no difference in the incidence of nausea (22.5% vs. 27.5%; RR: 0.81, CI 95%: 0.56 -1.25), but there was a lower incidence of vomiting (15% vs. 26.2%; RR: 0.57, CI 95%: 0.39 -1.05) in DH vs. DP group. At 24 hours pop we found no difference in the incidence of nausea (41.3% in DH vs. 52.5% in DP group; RR: 0.80, CI 95%: 0.57-1.1) but again a protective effect of vomiting (22.5% in DH vs. 41.25% in DP group; RR: 0.54; CI 95%: 0.31-0.86; p = 0.006). We found a clinically and statistically insignificant decrease of postoperative morphine requirements in DH group (3.2 mg vs. 4 mg), no difference in ocular opening time (8.3 min, DH vs. 8 min, DP) and Ramsay score at 30 min was > 2 in both groups (18.8 %, DH vs. 17.5%, DP). CONCLUSION: the addition of 1.5 mg of haloperidol to a standard dexamethasone prophylactic scheme for PONV is an effective strategy to control early and late vomiting but a non-conclusive strategy for decreasing the incidence of nausea.